Organizational Sustainability Through the Application of Holistic Human Resources Development Model (HHRDM) in Multi- National Companies of Penang, Malaysia - Arshad, Mohd Anuar; Mahmood, Arshad; Khan, Shahid; mullah, Kalee; Ahmed, Adeel; Shabbir, Muhammad Salman (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to explore the effective training programs for organizational Sustainability throw the application of holistic human resource development model of multi-national Company in Penang, Malaysia. This study highlights the significance of spiritual quotient (SQ) programmes in the formation process of human resource development (HRD). There were In-depth interview conducted from HR managers of 3 multinational companies in Penang to achieve the research objectives of this research. The findings divulged manifold problems that organisations lack understanding of the importance of SQ. It shows that SQ is the missing part of the process of employees’ development and should be considered an important factor to be developed. Moreover, the interest of SQ assures that SQ is embedded in the fabric of organisational behaviour and psychology. The study emphasises the vital influence of SQ on the bottom line of the organisation, whereby human resources can meaningfully contribute towards organisational sustainability. Further, this study indicates that without considering the spiritual development of employees, logic (IQ) and emotions (EQ) are not the only sources for human beings to perform utmost standard performances. Therefore, the emerging notion of human SQ and its multiple dimensions must be included in HRD initiatives in order to achieve a holistic mechanism. Based on these findings, this study proposed a holistic human resource development model for organisational effectiveness which will help to fulfil the rational, emotional and spiritual aspects of the employees.